Tolosa-Hunt syndrome masquerading as a carotid artery dissection - Taylor EJ (Dove Medical Press, 2014)
Elise J Taylor,1 Ursula M Anders,1 Joseph R Martel,1–4 James B Martel1–4 1Research Center, Martel Eye Medical Group, Rancho Cordova, 2Graduate Medical Education, California Northstate University College of Medicine, Elk Grove, 3Department of Ophthalmology, Sutter Medical Health, Sacramento, 4Department of Ophthalmology, Dignity Health, Carmichael, CA, USA Purpose: To demonstrate the difficulties of diagnosing a patient with Tolosa-Hunt syndrome (THS) due to its complicated presentation and extensive diagnostic testing, and how to manage the treatment of a patient in an emergent setting. Patients and methods: A female patient with THS affecting the left eye was examined using two magnetic resonance imaging (MRI) scans. The patient was treated with high-dose methylprednisolone (Solu-Medrol®) and prednisone. A follow-up MRI and magnetic resonance angiogram (MRA) was also performed 4 months later. Results: The second MRI scan disclosed a 5x9x10 mm lesion in the left superior orbital fissure/cavernous sinus. After administration of methylprednisolone and prednisone, the patient’s pain completely resolved, and the left eye regained full duction and eyelid mobility. The MRI and MRA obtained after the treatment showed no abnormalities. Conclusion: The rarity of THS makes it difficult to diagnose, especially when there is a question of accuracy and reproducibility of the testing performed. An ophthalmologic consultation in such cases is crucial. Keywords: granulomatous lesion, painful ophthalmoplegia, idiopathic orbital inflammation, multiple cranial nerve palsies